Principles and Practice of Case-based Clinical Reasoning Education: A Method for Preclinical Students - ten Cate, Olle; Custers, Eugène J.F.M; Durning, Steven J. (Innovation and Change in Professional Education, 2017)
assessment of clinical reasoning; diagnostic bias; diagnostic errors; dual process theory; scripts; medical problem-solving; peer teaching; problem-based learning; semantic qualifiers